1996
DOI: 10.5144/0256-4947.1996.633
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic, Conventional and Combination Phototherapy for Treatment of Nonhemolytic Hyperbilirubinemia in Neonates

Abstract: The objective of this prospective, randomized study was to compare the effectiveness of fiberoptic, conventional and a combination phototherapy in decreasing bilirubin concentrations in neonatal nonhemolytic hyperbilirubinemia. Forty-six infants who were 36 weeks' gestation and more were randomly assigned to fiberoptic phototherapy (n=16) (Biliblanket, Ohmeda), conventional daylight phototherapy (n=15) and combination phototherapy (n=15) (fiberoptic and conventional). The groups were similar in clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…In this study no side effects were reported in the beroptic phototherapy group. This was consistent with studies by Holtrop, Tan and Al-Alaiyan (7,14,16). Studies by Sarici, Rouf et al and Gutta et al observed a signi cantly higher incidence of skin rashes and loose stools in the conventional phototherapy group which was similar to our ndings (15,17,18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study no side effects were reported in the beroptic phototherapy group. This was consistent with studies by Holtrop, Tan and Al-Alaiyan (7,14,16). Studies by Sarici, Rouf et al and Gutta et al observed a signi cantly higher incidence of skin rashes and loose stools in the conventional phototherapy group which was similar to our ndings (15,17,18).…”
Section: Discussionsupporting
confidence: 93%
“…Phototherapy refers to the use of light of speci c wavelengths and doses to convert lipophilic bilirubin molecules in the body into water soluble isomers that can be excreted by the body to reduce TSB. Currently, there are several forms of phototherapy: conventional, beroptic and LED used in the treatment of hyperbilirubinaemia (7). The effectiveness of a phototherapy unit is determined by several factors, which include distance of light source from patient, surface area covered, wavelength and the irradiance of the phototherapy unit (8).…”
Section: Introductionmentioning
confidence: 99%
“…3 It is clear that irradiance is an important factor, with several studies showing that increased irradiance produces a faster decrease of serum bilirubin levels. 4 A dose-response relationship exists between the amount of irradiation and reduction in serum bilirubin, up to an irradiation level of 30-40 µW/ cm 2 /nm. Newer phototherapy units, when properly configured, and the use of reflecting curtains may deliver light energy up to 40 µW/cm 2 /nm, suggested to be the saturation level.…”
mentioning
confidence: 99%
“…An analysis of present study also demonstrated similar trends. 13 In previous studies, few side effects were reported with conventional therapy which includes imbalance of thermal environment and water loss, bronze baby syndrome, electrolyte disturbance, retinal damage, skin rashes, impairment of immune system and circadian rhythm disorder. In the present study, neonates exposed to conventional therapy were affected with few side effects such as skin rash (3; 5.5%), hyperthermia (2; 3.6%) and loose stools (1; 1.8%).…”
Section: Resultsmentioning
confidence: 99%